Atividade antibacteriana dos óleos essenciais de Origanum vulgare L. e Cinnamomum zeylanicum B. contra bactérias multirresistentes - Costa, Adalberto Coelho da (2009)
One of the largest world health problem is the bacteria resistance acquired to the antimicrobials, and that increases more and makes difficult their treatment. The nosocomial infections caused by these microorganisms difficultly will be eradicated by routine therapeutic methods, and even so, the antibiotics are considered the main therapeutic option. As alternative to treatment of those infections are considered the research of antimicrobials obtained of vegetable origin. The aim of this work was to determine the antibacterial activity of the essential oils obtained from Origanum vulgare L. and Cinnamomum zeylanicum B. against multiresistant bacteria strains; to identify the incidence of multiresistant pathogens as etiological agents of the infectious processes in nosocomial patients; to determine "in vitro" the minimum inhibitory concentration (MIC) of these referred oils against the bacteria whose growth was inhibited in the preliminary tests with the respective oils; to confirm the minimum bactericidal concentration (MBC) of the tested oils on the bacterial strains after the detection of CIM and to evaluate the interference of the studied oils using the bacterial kinetic curve. A preliminary "screening" was determined using the diffusion agar technique. The CIM was determined by the microdilution method, starting with solutions in the final concentrations of 8,0 up to 0,125%, obtaining the following results: The cinnamomum essential oil inhibited the multiplication of the bacteria in the following percentiles and concentrations: 95,83% - 8%; 91,66 - 2% and 79,1% - 1%. The origanum essential oil inhibited the bacteria multiplication in the respective percentile and concentrations of 75% - 0,125%; 83,33 - 0,25% and 100% - 0,5%. Based in the obtained data could be affirmed that in these studies the isolated bacterial strains such as Enterococcus faecalis, Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Acinetobacter baumannii and Pseudomonas aeruginosa were considered multiresistant to the tested antibiotics The C. zeylanicum B. essential oil was effective as bacteriostatic agent on 92% of the bacterial strains in with the CIM or 2%, and 4% of efficacy in CIM of 0,125%. The C. zeylanicum B. essential oil didn't reveal bactericidal properties, when tested in the CBM's of the considered microorganisms. The O. vulgare L essential oil demonstrated bactericidal activity in about the totality of the Gram positive and Gram negative bacteria studied, using a CBM of 0,5%. The bactericidal effect of the O. vulgare L. observed in the study against multiresistant bacteria, it was a very important die, considering that the found acquired values resemble each other with the drugs of last generation used in the research. In the bacterial kinetics the essential oils of C. zeylanicum B. and O. vulgare L. inhibited the microorganisms growth of the tested in the interval from 0,0 to 120 minutes. The antimicrobial values of the tested essential oils found in the experiments conduct or indicate to the application of new methodologies, looking for the way to a rational use of the same ones in the antibacterial therapeutics.